The Role of Teachers in the Formation of Students' Morals At MINU As Sabilillah Pilangsari Beji - Zain, Asmuni (AL MURABBI, 2025)
This study aims to examine the role of teachers in developing students’ noble character at Madrasah Ibtidaiyah Nahdlatul Ulama (MINU) Pilangsari, Beji. The formation of noble character (akhlaq al-karimah) in children is a fundamental objective of education and constitutes one of the primary responsibilities of teachers, particularly within Islamic-based educational institutions. In the context of contemporary challenges such as moral degradation and the weakening of ethical values among students, the role of teachers becomes increasingly strategic and essential.This research employs a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation. These methods are used to capture a comprehensive understanding of teachers’ practices, strategies, and experiences in fostering students’ character development. The findings indicate that schools, through the active involvement of teachers, play a crucial role in shaping students’ noble character. Teachers function not only as transmitters of academic knowledge but also as moral role models, mentors, and guides in practicing Islamic values in daily life.Various approaches are implemented by teachers, including the integration of religious and moral values into classroom instruction, habituation through exemplary behavior, and the reinforcement of character education via religious routines and ethical activities within the school environment. Through these efforts, teachers contribute significantly to cultivating students who possess strong moral integrity, discipline, and social responsibility in accordance with Islamic teachings.